Enhancing Students’ Listening Comprehension on Recount Text through Audio Recording Media - Intan Cezya Sijabat; Selviana Napitupulu (Young Journal of Social Sciences and Humanities, 2026)
Listening comprehension is a foundational yet challenging skill for EFL learners in Indonesia, primarily due to limited exposure to authentic spoken English and natural pronunciation. This study aims to evaluate the effectiveness of audio recording media in enhancing the listening comprehension of recount texts among tenth-grade students. Using a descriptive quantitative method, the research involved 33 students at SMA Tamansiswa Pematangsiantar as participants. Data were gathered through pre-test and post-test procedures utilizing a fill-in-the-blank listening instrument based on the recount text “My Holiday in Bali.” The findings demonstrate a substantial improvement in students' listening performance, with the mean score rising from 40.00 in the pre-test to 79.09 in the post-test, reflecting a 97.7% increase. Furthermore, the percentage of students meeting the Minimum Mastery Criterion (KKM ≥ 75) surged from 6.1% to 66.7%. The results indicate that audio recording media fosters a conducive learning environment by providing repeated exposure, enhancing auditory resilience, and allowing students to internalize linguistic input at their own pace. Pedagogically, this study underscores the necessity of integrating technology-driven media to support student-centered and contextualized learning, fully aligning with the Merdeka Belajar framework to cultivate more autonomous and motivated learners.